Analytically continued fock space multi-reference coupled-cluster theory: application to the shape resonance - Pal, Sourav; Sajeev, Y.; Vaval, Nayana (Chemical Physics, 2006)
The Fock space multi-reference coupled-cluster (FSMRCC) method is used for the study of the shape resonance energy and width in an electron-atom/molecule collision. The procedure is based upon combining a complex absorbing potential (CAP) with FSMRCC theory. Accurate resonance parameters are obtained by solving a small non-Hermitian eigen-value problem. We study the shape resonances in e(-)-C2H4 and e(-)-Mg. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: complex absorbing potential; correlated independent particle potential; Fock space multi-reference coupled-cluster theory; shape resonance